Emerging Threat of Multidrug Resistant Pathogens From Neonatal Sepsis - Zou, Hua; Jia, Xiaojiong; He, Xiao; Su, Yan; Zhou, Ligang; Shen, Yan; Sheng, Chenglin; Liao, Ang; Li, Chunli; Li, Qiuhong (Frontiers in Cellular and Infection Microbiology, 2021)
Multidrug-resistant (MDR) pathogens are responsible for a substantial burden of morbidity and mortality from neonatal sepsis; however, data on these sepsis-related pathogens among hospitalized neonates in China are not well characterized. In this study, a total of 240 strains were isolated from four Women and Children’s hospitals in Southwest China between 2014 and 2019. Of these included pathogens, 104 (43.33%) were gram-positive bacteria, 129 (53.75%) were gram-negative bacteria, and 7 (2.92%) were fungi. Escherichia coli (E. coli, 34.01%) and Klebsiella pneumoniae (K. pneumoniae, 15.35%) were the main pathogen of neonate bacteremia. ST167 were the most prevalent STs in E. coli and ST11 in K. pneumoniae. Our study found that E. coli (62.71%) was the predominate pathogen of early-onset sepsis, among which 64.86% were MDR. Late-onset sepsis was mainly caused by K. pneumoniae (28.31%) and E. coli (24.78%), with showing that 78.33% of these pathogens were MDR. Notably, the prevalence of EO/LO pathogens were quite different from Indian and south of China. Moreover, we found that blaCTX-M (42.06%) was most dominant resistant genes with about a third isolates (31.09%) were positive for blaCTX-M-15. All the carbapenem-resistant K. pneumoniae were positive for NDM-1. Moreover, late-onset sepsis and antibiotic exposure were significantly associated with MDR infection. Emerging multi-resistant pathogens of sepsis posts a serious threat to neonatal outcomes and emphasizes an urgent need to control their further spread.